4D Numerical Analysis of Scaffolds: A New Approach - André Vieira (2014)
A large range of biodegradable polymers are used to produce scaffolds for tissue engineering, which temporarily replace the biomechanical functions of a biologic tissue while it progressively regenerates its capacities. However, the mechanical behavior of biodegradable materials during its degradation, which is an important aspect of the scaffold design, is still an unexplored subject. For a biodegradable scaffold, performance will decrease along its degradation, ideally in accordance to the regeneration of the biologic tissue, avoiding the stress shielding effect or the premature rupture. In this chapter, a new numerical approach to predict the mechanical behavior of complex 3D scaffolds during degradation time (the 4th dimension) is presented. The degradation of mechanical properties should ideally be compatible to the tissue regeneration. With this new approach, an iterative process of optimization is possible to achieve an ideal solution in terms of mechanical behavior and degradation time. The scaffold can therefore be pre-validated in terms of functional compatibility. An example of application of this approach is demonstrated at the end of this chapter.